PROGNOSTIC VALUE OF THE IMMUNOHISTOCHEMICAL MARKERS KI-67 AND P53 AFTER RADICAL PROSTATECTOMY - M. V. Kovylina (Onkourologiâ, 2014)
Background. Prostate cancer (PC) is one of the most common malignant tumors in men. The total Gleason (Gleason index) scores are one of the most important prognostic factors in patients with PC. The expression of p53 and Ki-67 proteins is also considered as a prognostic factor.Objective: to estimate the frequency with which the expression of these proteins shows up and to compare the findings with Gleason scores.Materials and methods. This investigation studied prostatic drugs after radical prostatectomy. The Gleason scale was use to rate the grade of a tumor. The expression of Ki-67 and p53 was an immunohistochemical method. The data were statistically processed using Spearman’s cor-relation test.Results. Based on the Gleason index, all the tumors were divided into 3 groups: 1) low grade (4–6 scores); 2) intermediate grade (7 scores); 3) high grade (8–10 scores). Group 1 included 5 (16 %) patients; Group 2 and 3 consisted of 19 (64 %) and 6 (20 %) patients, respectively. The expression of p53 and Ki-67 was observed in none of the low-grade tumor samples. There was a statistically significant relationship between higher Ki-67 proliferation and higher Gleason scores.Conclusion. In accordance with the results of this investigation, the expression of the marker Ki-67 can be used as a prognostic factor in PC. At the same time, a possible relationship between p53 expression and prognosis in PC calls for further investigation.